Residency restrictions, race, and homelessness among registered sex offenders - Suiter, Emily (Criminal justice studies, 2022)
In recent decades, the number of individuals on sex offender registries has increased, many of whom are subject to codified residency restrictions that forbid residing within certain geographic locations and therefore limit viable housing options. As a result, many convicted sex offenders struggle with unstable housing and homelessness. While there is a growing body of research concerning residency restrictions and unstable housing among sex offenders, no study, to our knowledge, has explored whether the association between residency restrictions and homelessness is stronger for Black and Hispanic registrants. Using data from the Chicago Sex Offender Registry, this study examined of the relationship between residency restrictions and sex offender homelessness. Registrants subject to residency restrictions had a substantially higher risk of homelessness than their counterparts. Furthermore, residency restriction status and race interacted in their association with homelessness, such that the deleterious impact of residency restrictions was magnified for Black registrants. The results of the analyses demonstrate that Black sex offender registrants disproportionately disadvantaged by residency restrictions and highlight the importance of developing evidence-based monitoring strategies that prevent and end homelessness among convicted sex offenders.